The Effects of Amide Groups on the Thermal and Optical Properties of Poly(amide‐imide)s with Low Residual Stress for Microelectronic Devices. Issue 10 (29th February 2016) - Kim, Kwangin; Yoo, Taewon; Ha, Hyemin; Kim, Jinyoung; Han, Patrick; Han, Haksoo
Abstract : In this study, poly(amide‐imide)s are synthesized for electronic materials by adding amide groups into polyimide. As it is expected, poly(amide‐imide) shows an amorphous structure with a lower glass transition temperature and residual stress than the neat polyimide due to the high steric hindrance of the amide group. Also, the modification to the polyimide structure leads to higher transmittance and enhances colorless properties. Consequently, successful synthesis of poly(amide‐imide)s is demonstrated which has wide applicability in the electronic industries due to their low glass transition temperature. It is expected that semiconductor and integrated circuit products can be manufactured utilizing poly(amide‐imide)s with high reliability and a low chance of cracking due to their lower residual stress. Furthermore, it envisioned that the improved optical properties of poly(amide‐imide) materials will allow for their applications in transparent displays and coating products. Abstract : Generally, between polymer and substrate has high residual stress. In the case of poly(amide‐imide)s, they shows decrease of residual stress on cooling step so it is more safe for electronic device products such as semiconductor and integrated circuit.